2019
DOI: 10.3390/su11082340
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Spatial and Temporal Distribution of Process Gases within Municipal Biowaste Compost

Abstract: Composting processes reduce the weight and volume of biowaste and produce products that can be used in agriculture (e.g., as fertilizer). Despite the benefits of composting, there are also problems such as odors and the emission of pollutants into the atmosphere. This research aimed to investigate the phenomenon of process gas (CO, CO2, NO, O2) evolution within a large-scale municipal composter. The effects of turning frequency and pile location (outdoor vs. indoors) on process gas and temperature spatial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 52 publications
(94 reference statements)
3
30
0
Order By: Relevance
“…Much of the microbial activity occurs in tropical regions where temperatures are consistently high (>30°C) and damp enough to support thriving microcosm (Liu et al, 2018). CO is also generated during municipal biowaste composting, which was confirmed in our earlier study (Stegenta et al, 2018, 2019a,b), but the biotic and abiotic factors causing it are still not well-understood. Measured CO concentrations were high, thus raising concerns about occupational safety for workers and local air quality.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Much of the microbial activity occurs in tropical regions where temperatures are consistently high (>30°C) and damp enough to support thriving microcosm (Liu et al, 2018). CO is also generated during municipal biowaste composting, which was confirmed in our earlier study (Stegenta et al, 2018, 2019a,b), but the biotic and abiotic factors causing it are still not well-understood. Measured CO concentrations were high, thus raising concerns about occupational safety for workers and local air quality.…”
Section: Introductionsupporting
confidence: 68%
“…However, the precise knowledge of chemical pathways influenced by thermal degradation in natural systems remains elusive due to the numerous interacting processes and conditions observed in composting organic materials, such as microbial activity and the heterogeneous availability of O 2 (Cowan et al, 2018). However, our previous studies (Stegenta et al, 2018, 2019b) shown that the concentrations of CO in an aerobic composting pile are significant (>1,000 ppm). Additionally, there is an immediate need to drastically reduce emissions in order to limit climate change (Liew et al, 2016).…”
Section: Introductionmentioning
confidence: 76%
“…CO is formed as a result of the biological decomposition of the OF together with other gases such as CO 2 , CH 4 , H 2 , nitrogen compounds, volatile organic compounds (VOCs), and H 2 S [15]. CO formation has been observed during composting of green waste [16], green waste with manure [17], organic waste [18,19], and municipal waste [20,21]. The discovery of CO formation during composting was unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…The authors recommend deleting this data, for statistical calculations, due to unknown real values. The procedure of calibration of the Kigaz 300 analyzer was as described in our previous study [18]. Each time the analyzer was started, it performed a 2 min autocalibration.…”
Section: Measurements Of Gas Concentrations In the Reactorsmentioning
confidence: 99%
See 1 more Smart Citation